THE PROBLEM STUDY METHOD AS AN EFFECTIVE MEANS FOR FORMING CRITICAL THINKING AND LANGUAGE SKILLS IN STUDENTS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This work examines the problem-based learning method as an active approach that allows students to encounter real or simulated problems, contributing to the development of critical thinking and creative abilities. As a practical example, the use of the “literary evolution” method in the literature curriculum is described, where students explore the influence of classical works on modern literature.
Keywords: problem-based learning method, critical thinking, creative abilities, problem-based tasks, research method, learning motivation, educational process, students' independence.